Small molecule degraders of the hepatitis C virus protease reduce susceptibility to resistance mutations - Mélissanne de Wispelaere (Nature Portfolio, 2019)
Targeted protein degradation (TPD) is a promising strategy for drug development. In this proof-of-concept study, the authors use telaprevir, which binds hepatitis C virus (HCV) NS3/4A protease, to target the protease for protein degradation, and show inhibition of wildtype as well as drug resistant HCV.